Elaboration of tetravalent antibody responses against dengue viruses using a subunit vaccine comprised of a single consensus dengue envelope sequence. Issue 46 (1st November 2017) - Sun, Jin; Li, Min; Wang, Yinan; Hao, Pei; Jin, Xia
Abstract: Dengue viruses (DENVs) are re-emerging pathogens transmitted by mosquitoes mainly in tropical and subtropical regions. Each year, they are estimated to infect 390 million people globally. The major challenge confronting dengue vaccine development is the need to induce balanced, long lasting tetravalent immune responses against four co-circulating virus serotypes (DENV-I, -II, -III, -IV), because primary infection by any one of which may predispose infected individuals to more severe diseases during a heterotypic secondary infection. Another difficulty is to select representative strains in vaccine design to provide cross-protection against most circulating virus strains. In this study, aimed at developing a tetravalent subunit vaccine with a representative single protein, we designed two vaccines (named cE80(D4) and cE80(max)) based on the consensus sequences of the ectodomain of envelope protein of 3127 DENV strains, and then expressed them in the baculovirus expression system. Both vaccines were capable of eliciting specific antibodies against all four DENV serotypes, and the predominant IgG subtype elicited by the two vaccines was IgG1. Moreover, these vaccines activated both type I and type II antigen-specific helper T cells that secreted IFN-γ and IL-4, respectively. This proof-of-concept study has set foundation for further optimization of a single protein-based tetravalent DENV vaccine.